Postcolonialité et archive : le cas du roman de l’après-guerre et l’héritage du conflit armé au Guatemala - Mónica Quijano (Amnis)
One of the paths that postcolonial criticism has taken in discussions of literary discourse in Latin America, is the one that questions the status of the written testimony of individuals belonging to subaltern groups. Its main exponent was the text written by Elisabeth Burgos, Me llamo Rigoberta Menchú, y así me nación la conciencia (1983), where the Venezuelan anthropologist transcribed Menchú's testimony about the injustice suffered by Guatemalan peasant communities during the second half of twentieth century. This discussion allowed to question the legitimacy of literary discourse, seen as heir of colonialism. First, because it imposed writing as the only legitimate means for the transmission of knowledge and aesthetic practices. Second, because the intellectual elites appropriated this discourse, which left out all speech not belonging to the tradition created by these circles. It is from this discussion that I propose to analyze the literary response to these criticisms, through three novels written by Central American authors: Señores bajo lo árboles o Breve relación de la destrucción del indio de Roberto Morales, Insensatez de Horacio Castellanos Moya and El material humano de Rodrigo Rey Rosa. These writers suggested, by working with the archive (oral or written), a means of aesthetic reflection of what happened in the recent history of Guatemala and the possibility that the writer can "speak" in the place of another, in this case, the victims of the civil war that occurred between 1966 and 1982.